The phenomenon of twin’s deficits in the Libyan economy: Testing short and long-run relationships between fiscal budget deficit and current account deficit( ) in Libya (Economic studies journal, 2025)
The motivation behind this paper is to explore the dynamic relation between budget deficit and real non-oil trade deficit in the short and the long run, with a consideration of other related factors including oil revenue, the real exchange rate, the real non-oil GDP and domestic prices in Libya from 1984 to 2022. The empirical analysis that applies SVAR with its impulse response function simulations with some cointegrated relations and further simulation using ARDL provide, evidence for both the short run and long run dynamics between the variables. The results revel that there is a kind of correlation between the deficit in the real non-oil trade and the deficit in real fiscal budget. Imperfect budgetary policy associated with aplenty of oil revenue where more is spent on consumption than investment) Concurrent with the inefficient tax system (resulting in a deficit in the fiscal budget and this late exacerbates the real non-oil trade deficit via increased spending on imported consumer goods. policy implication in this paper supports the view that to obtain a development in the non-oil trade blend the GDP of the non-oil sector, increased government spending for investment, should be of the major focus for the policymakers.
Keywords: Fiscal Budget; Trade Balance; win’s deficits; real GDP, CPI and (AFD, VECM, SVAR, IRF, ARDL & DV, Causality tests) tests & techniques